Pengaruh Variasi Konsentrasi H3PO4 Sebagai Zat Aktivator Terhadap Karakteristik Karbon Aktif dari Sekam Padi - Dwityaningsih, Rosita; Rahayu, Theresia Evila Purwanti Sri; Handayani, Murni; Nurhilal, Mohammad (Infotekmesin, 2023)
Rice husk is an organic material that has a high lignocellulosic content so it has the potential to be turned into activated carbon. One method of making activated carbon is activation with a phosphoric acid activator (H3PO4). The purpose of this research was to study the effect of varying concentrations of H3PO4 as an activator on the characteristics of rice husk-activated carbon. The characterization refers to SNI 06-3730-1995 regarding the technical quality requirements of activated charcoal. Activation of rice husk carbon was carried out by contacting the carbon with H3PO4 for 24 hours and shaking it. The H3PO4 consisted of 3 concentration variations, namely 4M, 6M, and 8M. From the research results, the water content was 3.936%; 4.037%; 4.070%, the absorption of iodine has met the character of activated charcoal according to SNI, namely 1217.204 mg/g; 1204.255 mg/g; 1184.832 mg/g while the ash content value does not meet the SNI standard, which is still above 10%. The highest adsorption capacity and adsorption efficiency could be activated with 8M H3PO4, namely 22.42 mg/g and 89.68%. IR spectra on activated carbon with three variations of H3PO4 concentration showed the presence of aromatic C-H, C=C, and C-O anhydride functional groups.